Possible evidence of remotely triggered and delayed seismicity due to the 2001 Bhuj earthquake (Mw = 7.6) in western India - Surve, G.; Mohan, G. (My University, 2012)
Remote triggering by large earthquakes at regional distances is a globally observed phenomenon. However, there are no reports of observations of dynamic triggering at regional distances of several source lengths associated with the large Mw = 7.6 Bhuj earthquake of January 26, 2001, in western India. In the present study, a swarm of over 140 microearthquakes that occurred about 500 km southeast of Bhuj, in the geothermal province of the Western Ghats in the Deccan volcanic province (DVP) of India, immediately after the occurrence of the Bhuj earthquake in 2001 is investigated. The post-Bhuj seismicity (M < 2.0) occurred in three bursts spread over 2 months with each burst of intense activity lasting for 2–3 days. All the three bursts of seismicity occurred in the same volume along a 5-km-long NW–SE trending fault. The temporal coincidence and the sudden rise in seismicity that interrupts the characteristically low background seismicity strongly suggest that the Bhuj earthquake may have remotely triggered this activity. The triggered seismicity began approximately 2.5 h after the onset of the Bhuj mainshock and continued well after the passage of the surface waves, suggesting that the dynamic stresses possibly gave rise to secondary time-dependent mechanisms leading to the triggering. It is proposed that the triggered and delayed seismicity is possibly a consequence of the redistribution in pore fluid pressure due to the Bhuj earthquake. This is the first documented observation of remotely triggered seismicity at regional distances due to the Bhuj earthquake.
Keywords: Triggered seismicity; Coulomb stress; Western Ghats; Bhuj earthquake; Geothermal